Contexts, analogies, and tasks that expose the purpose of the key concepts of probability - Borovcnik, Manfred (Universidade Estadual de Campinas, 2020)
Probability is and will continue to be a virtual concept. This specificity requires meta strategies that go far beyond the instruction of the mathematical details and ask for a sensible use of simulation. We suggest focussing teaching efforts on explicitly exposing the students to the purpose of the concept of probability. The purpose shows the character of probability indirectly as the required steps for solving a task make the properties appear natural in the context. We elaborate suitable tasks and interactive animations, which are designed to overcome learning obstacles. We focus on three aspects of probability: The character of probabilistic statements, the transparent use of probability for decisions under risk, and informal inference considerations in the early probability education. An essential criterion of teaching is how far it allows learners a more direct access to the concepts on an intuitive level. For designing didactic animations, our principles are characterised by the following ideas: A dynamic change is explored in comparison to the initial situation. Like watching a video, one looks at the different stages of emergence of a relation between the investigated concepts.